Controlled surface/interface structure and spin enabled superior properties and biocompatibility of cobalt ferrite nanoparticles - Ansari, Sumayya M.; Sinha, Bhavesh B.; Pai, Kalpana R.; Bhat, Suresh K.; Ma, Yuan-Ron; Sen, Debasis; Kolekar, Yesh D.; Ramana, C., V. (Allied Surface Science, 2018)
High quality, crystalline, well-dispersed, and stable magnetic oxide nanoparticles (NPs) of inverse spinel cobalt ferrite (CoFe2O4; CFO) were prepared by a facile, reproducible, and simple hydrothermal route. The transmission electron microscopy, small-angle scattering and X-ray diffraction analyses demonstrate the structural quality of CFO NPs with a controlled size of similar to 12 nm. Small-angle scattering experiments demonstrate that the pristine CFO NPs have the individual size similar to 8.5 nm and spherical shape. The Raman and infrared spectroscopic measurements further confirm their high chemical quality and cubic symmetry. CFO NPs exhibit a remarkable, maximum coercivity (H-c) value of 18.92 kOe, which is the highest value achieved to date. Surface spins and spins canting along with a weak dipolar interaction accounts for the giant H-c and large effective anisotropy (11.45 x 10(6) erg/cm(3)) of these CFO NPs. The magnetic grain size of NPs reveals that the canted surface spins exist around the magnetic particles. Reorientation of surface spins and interparticle interaction causes the jumping behaviour in M-H hysteresis loops at H = 0. The cell viability of CFO NPs against the cancer (cisplatin resistant ovarian cancer - A2780/CP70) was evaluated to determine their potential application in biomedicine and health science. The mild response of CFO NPs in terms of their anti-proliferative nature against cancer cells and negligible cytotoxicity suggests their human-safe-and-friendly nature which makes them suitable for biomedical/health-related applications. Assessment of toxicity toward human red blood cells (RBC) revealed that hemolysis is less than 5% compared to the positive control confirming the potential applications of CFO NPs targeting human cells and making relevant for adopting them in biomedicine.